Prevalence of Hepatitis B infection among the Pregnant Women of Forcibly Displaced Myanmar Nationals in a Selected Rohingya Camp (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Hepatitis B is a viral infection that affects the liver and causes both acute and chronic diseases. It spreads through contact with the blood or other body fluids of an infected person. The best way to prevent hepatitis B is to get vaccinated. Treatment options for chronic hepatitis B include antiviral medications and liver transplantation. Hepatitis B virus can easily pass from a pregnant woman with hepatitis B to her baby at birth. In the Forcibly Displaced Myanmar National's camp, Hepatitis B is affecting more and more mothers and children day by day at an alarming rate.Objective: This study aimed to find out the prevalence of Hepatitis B among the pregnant women of Forcibly Displaced Myanmar National people.Methodology: This was a cross-sectional study conducted on pregnant women who have visited OPD of Maternal and Child Health Care Centre by Human Aid Bangladesh in Balukhali camp 9, Ukhiya, Cox's Bazar. A total of 465 subjects were included in the study. The respondents were interviewed and information was recorded in the questionnaire. The laboratory investigation was done and collected from the patient on spot from the facility. Ethical issues were maintained and the results were obtained to complete the data sheet analyzed by SPSS, Z test, t-test, Chi-Square test.Results: A total of 465 respondents were interviewed and tested for hepatitis B infection by HbsAg strip test by ICT method. In the study 53(11.40%) of the respondents were found positive for hepatitis B infection. Most of the respondents were illiterate 153(32.90%). The maximum respondents were in the age range of 16-20 years (61.94%). Very few respondents were known for hepatitis B infection. 24(5.1%). Among the respondents, 21(4.52%) had a positive partner or family member. Most of the respondents 368(79.14)were not vaccinated.Conclusion: The prevalence of Hepatitis B Infection among Pregnant women of Forcibly Displaced Myanmar National is quite high. Lack of knowledge, poverty, lack of vaccination, and violence contributed behind the high rate of Hepatitis B Infection among them.J. Dhaka National Med. Coll. Hos. 2023; 29 (02): 32-37